Species - Mancuso, Frank Jr; Feldman, Dennis; Kingsley, Ben; Madsen, Michael; Molina, Alfred; Whitaker, Forest; Helgenberger, Marg; Henstridge, Natasha; Donaldson, Roger; Egerton, Mark; Streit, David; Geiger, H.R; et al. (Viva Video Inc., 1995)
When a creature genetically engineered through extraterrestrial intelligence escapes from observation, scientist Xavier Fitch assembles an elite team of experts to track it down. These experts--a government assassin, an "empath", a biologist and an anthropologist combine their expertise and trace their prey to Los Angeles. There, in the form of a stunning young woman, the alien initiates a horrific plan: to mate with unsuspecting men and produce offspring that could destroy mankind. As her deadly biological clock ticks rapidly, Fitch and his team are hurled into a pulse-pounding chase in which the fate of humanity itself hangs in the balance.